The British Art Show. : recent paintings and sculpture by 112 artists - Drew, Joanna; Harrison, Michael; Packer, William; Mappin Art Gallery, Sheffield; Laing Art Gallery, Newcastle upon Tyne; Hatton Gallery, University of Newcastle (London : Arts Council of Great Britain, 1979)
Abbott, John ; Abrahams, Ivor ; Adams, Norman ; Andrews, Michael ; Ball, Martin ; Bellany, John ; Berg, Adrian ; Bergman, Stephenie ; Blackadder, Elizabeth ; Bowling, Frank ; Buckley, Stephen ; Camp, Jefferey ; Caro, Anthony ; Carter, John ; Carter, Tony ; Clough, Prunella ; Cubb, John ; Cocker, Doug ; Cook, Barrie ; Crabtree, Jack ; Creffield, Dennis ; Crowther, Michael ; Davison, Francis ; Draper, Kenneth ; Edwards, John ; Eyton, Anthony ; Fielding, Brian ; Freud, Lucian ; Frost, Terry ; Fulton, Hamish ; Gibson, Lloyd ; Ginsborg, Michael ; Greaves, Derrick ; Green, Alan ; Green, Anthony ; Groom, Jon ; Hall, Nigel ; Hambling, Maggi ; Hilliard, John ; Hockney, David ; Hodgkin, Howard ; Hodgson, Carole ; Holland, Harry ; Hoyland, John ; Hughes, Patrick ; Huxley, Paul ; Inlander, Henry ; Irvin, Albert ; Jones, Allen ; Jones, Wynn ; Kempsell, Jake ; Kenny, Michael ; King, Dave ; King, Phillip ; Kossoff, Leon ; Leapman, Edwina ; Lee, Terry ; Loker, John ; Long, Richard ; Lyons, Michael ; McComb, Leonard ; Macfarlane, John Foster ; McLean, John ; Maine, John ; Martin, Barry ; Mason, Michael ; Mason, Robert ; Mayer, Michael ; Milow, Keith ; Milroy, Jack ; Monro, Nicholas ; Mylius, Andrew ; Nathan, Janet ; Naylor, Martin ; Neagu, Paul ; Newsome, Victor ; Oliver, Ken ; Peacock, Brian ; Peel, Michael ; Pietsch, Heinz dieter ; Pope, Nicholas ; Preece, Lawrence ; Pye, William ; Read, Simon ; Reeves, Keith ; Riley, Bridget ; Rippon, Peter ; Rogers, Will ; Rose, Kate ; Russell, Bruce ; Sandle, Michael ; Scobie, Gavin ; Scott, Bill ; Scully, Sean ; Selway, John ; Snook, Harry ; Stevens, Norman ; Thompson, Brian ; Tindle, David ; Uglow, Euan ; Upton, Michael ; Walker, John ; Walker, Margaret ; Barker, David Walker - ; Weschke, Karl ; Whishaw, Anthony ; White, Caroline ; etc.
biografie
The British Art Show, Mappin Art Gallery, Sheffield, 1 December 1979 to 27 January 1980 : Laing Art Gallery, Newcastle upon Tyne and Hatton Gallery, University of Newcastle, 15 February 1980 to 23 March 1980 ; Arnolfini Gallery, Bristol and Royal West of England Academy in conjunction with City Museum and Art Gallery, 18 April 1980 to 24 May 1980
Engels
boek